2015
DOI: 10.1186/s12889-015-1642-4
|View full text |Cite
|
Sign up to set email alerts
|

Trends of rubella incidence during a 5-year period of case based surveillance in Zimbabwe

Abstract: BackgroundRubella is a disease of public health significance owing to its adverse effects during pregnancy and on pregnancy outcomes. Women who contract rubella virus during pregnancy may experience complications such as foetal death or give birth to babies born with congenital rubella syndrome. Vaccination against rubella is the most effective and economical approach to control the disease, and to avoid the long term effects and high costs of care for children with congenital rubella syndrome as well as to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
31
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 15 publications
16
31
4
Order By: Relevance
“…About 93.1% of rubella confirmed cases were among <15 years old children and rubella reached its peak incidence in children between 3 and 6 years of age. This was similar to finding from a study in Zimbabwe [13]. The low incidence of rubella cases in persons older than 15 years is likely due to natural infection and development of immunity against rubella at earlier ages.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…About 93.1% of rubella confirmed cases were among <15 years old children and rubella reached its peak incidence in children between 3 and 6 years of age. This was similar to finding from a study in Zimbabwe [13]. The low incidence of rubella cases in persons older than 15 years is likely due to natural infection and development of immunity against rubella at earlier ages.…”
Section: Discussionsupporting
confidence: 90%
“…The proportion of rubella positive cases increased from 4.2% (83) in 2009 to 23.9% (856) in 2013 but dropped to 10.6% (222 cases) and 15.3% (319 cases) in 2014 and 2015 respectively. This was higher than previous findings from Ethiopia [11] and Abia State of Nigeria [12] and was lower than a finding of 37.6% from Zimbabwe [13]. The increasing number of laboratory confirmations might be related with improvement in surveillance sensitivity, quality and coverage.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…In this study, 17.3% of non-measles cases were found positive for rubella virus and children 5–9 years were affected greatly. This finding was much lower than a 37.6% positivity rate of rubella from Zimbabwe [17]. In general, 43.2% of laboratory tested samples were positive for either measles or rubella.…”
Section: Discussionmentioning
confidence: 77%
“…In a recent review of literature, Goodson [2] reported rubella Immunoglobulin M (IgM) positivity rates among suspected measles cases ranging from 14 to 40% in the World Health Organization African Region between 2002 and 2009. Descriptive studies on measles surveillance programs in Africa indicate higher acute rubella positivity rates among the 5-9 years [2, 3] and 10-14 years age group [4,5].…”
Section: Introductionmentioning
confidence: 99%